The Influence of Competence and Work Environment to Improve the Performance of ASN Employees By Work Motivation as an Intervening Variable at the Regional Secretariat Kota Tebing Tinggi - Afridayani Damanik; Sri Rahayu; Kiki Farida Ferine (Riviera Publishing, 2025)
This study aims to analyze the influence of competence and work environment on improving the performance of State Civil Apparatus (ASN) employees, with work motivation as an intervening variable in the Regional Secretariat of Tebing Tinggi City. The study uses a quantitative method with a survey approach, distributing questionnaires to ASN employees. Data analysis was performed using path analysis to determine both direct and indirect effects between variables. The results show that competence and work environment have a positive and significant effect on work motivation and performance improvement. Competence (X1) positively influences work motivation (Z) with a path coefficient of 0.502 and performance improvement (Y) with a path coefficient of 0.444. Work environment (X2) positively influences work motivation (Z) with a path coefficient of 0.369, and performance improvement (Y) with a path coefficient of 0.404. Work motivation (Z) positively affects performance improvement (Y) with a path coefficient of 1.017. Performance improvement (Y) significantly mediates the relationship between competencies (X1) and work motivation, as well as between the work environment (X2) and work motivation. These findings confirm that optimizing ASN performance can be achieved by enhancing competencies, fostering a supportive work environment, and increasing work motivation.